Meaningful Work as the Moderator of Increasing Challenging Job Demands and Job Boredom in Generation Y Workers - Afiyah Tsarwat Zharifah; Endang Parahyanti (Journal An-Nafs: Kajian Penelitian Psikologi, 2022)
Job boredom is more often experienced by generation Y workers. This can be reduced by increasing challenging job demands. However, this factor does not always provide a long period to reduce job boredom. The existing phenomenon also shows that not only challenges, generation Y workers also want meaningful work. This study aimed to see the moderating effect of meaningful work in the relationship between increasing challenging job demands and job boredom in generation Y workers. Sampling was conducted on 327 generation Y workers (aged 23-40 years) throughout Indonesia. The data collection method used a questionnaire on job boredom (âˆ = 0.714), increasing challenging job demands (âˆ = 0.832), and meaningful work (âˆ = 0.929). The main data analysis technique was using moderated multiple regression analysis. This result showed that meaningful work was a moderator in the relationship between increasing challenging job demands and job boredom. Increasing challenging job demands itself could reduce job boredom, but the result showed that meaningful work was more consistent in reducing job boredom than increasing challenging job demands. Therefore, besides providing challenges, meaningful work is also important to get the organizationâ€™s attention so the workers, especially Generation Y, do not experience job boredom.